ESTIMATION OF ESTROGEN AND PROGESTERONE AFTER LAPAROSCOPIC OVARIOCTOMY IN BITCHES - Wisam Ghanim Sahar Abd Al Bari Abbas Al-fars (Basrah Journal of Veterinary Research)
This study was planned to assess the effect of laparoscopic ovarioctomy in bitches on estrogen and progesterone hormones levels pre and post operation . The hormonal analysis was performed by Serum which was extracted from blood samples , the hormonal test include ( estrogen and progesterone ) , by using a device called Mini vidas system hormones assay with the kit of Bio merio of same company and then results were recorded , which include decrease in level of ( estrogen and progesterone ) post operation in two groups , but the level of depression in group B ( bilateral laparoscopic ovarioctomy ) more than group A ( unilateral laparoscopic ovarioctomy